EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DENGAN GALLERY OF LEARNING PADA POKOK BAHASAN BANGUN RUANG SISI LENGKUNG DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VIII SMP N SE-KABUPATEN BOJONEGORO TAHUN PELAJARAN 2013/2014 - Khoirutunnisa, Anis Umi (MAGISTRA, 2015)
The research was conducted with the aim to determine: (1) which one results better mathermatics learning achievements between NHT with gallery of learning, NHT and conventional learning model, (2) wich one results better mathematics learning achievements with climbers,campers or quitters (3) on each learning models, which one gives better mathematics learning achievements students with climbers,campers or quitters (4) on each climbers,campers or quitterswich one gives better mathematics achievements between NHT with gallery of learning, NHT or conventional. This study was a quasi experimental research with 3x3 factorial designs. The balancedtest of the previous data (the result of UAS)was analyzed using one way ANOVA. The conclusion shows that the three classes have balance ability. The hypotheses testing used unbalanced two ways ANOVA.The conclution of the research were asfollows: (1) The students with NHT with Gallery of learning models have better learning achievement than the students with NHT learning models and conventional, and NHT learning models have better achievement than those with conventional learning; (2) theclimbers have better mathematics achievement than campers and quitters, and the campersthe achievement are better than those quitters; (3) a. In the NHT with gallery oflearning model, there was no difference in learning achievement in each criterion of Adversity Quotient (climbers,campersandquitters);b. In the NHT learning models, the climbersand campersthe mathematics achievement were better than quitters; c. In the conventional learning models, the campers mathematics achievement are better than climbersand quitters, and the campersthe achievement better than quitters. (4) a. For the climbers, there was no difference in learning achievement in each learning models; b. For the campersNHT with gallery learning and NHT better than conventional learning ;c. For the quittersNHT with Gallery of learning model produce better mathematics achievement than NHT learning model and Conventional learning. Kata kunci:NHTwith gallery of learning, NHT, conventional, Adversity quotient, andmathematics learning achievements.